Meningkatkan Kreatifitas Anak Menggunakan Media Kolase Biji-Bijian Di Paud Kasih Ibu - Neni Marlinda (Early Childhood Research and Practice, 2026)
The aim of this study was to determine the improvement in children's creativity through the use of seed-based collage media at PAUD Kasih Ibu in Kepahiang Regency. This study employed Classroom Action Research (CAR) methodology, utilizing a cyclical procedural approach. The subjects were 12 children from Group B at PAUD Kasih Ibu. The research was conducted over two cycles, with two meetings per cycle. Data analysis involved both qualitative and quantitative methods; qualitative analysis focused on process improvements expressed through descriptive ratings, while quantitative analysis measured outcome improvements using percentages. The results regarding the improvement of children's creativity using seed-based collage media showed the following achievement percentages: Cycle I, Meeting I (41.14%); Cycle I, Meeting II (53.64%); Cycle II, Meeting I (70.31%); and Cycle II, Meeting II (89.06%). The study concludes that children's creativity improved through the use of seed-based collage media at PAUD Kasih Ibu, Kepahiang Regency; by Cycle II, Meeting II, the achievement reached 89.06%, placing it in the "Developing Very Well" (BSB) category.